PEMBUATAN GAME “FLY SHOOTER” DENGAN KAMERA SMARTPHONE - Lukie Lukie; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
“Fly Shooter” is a  action and arcade game for Android. Where the player must collect as many point by shooting the flies within one minute. This game use two-dimensional graphics. The game is created with the purpose to use gyro sensor on smartphone into the game, insert augmented reality into the game with camera on the smartphone, and game development with unity. This game created by Unity game engine with C# as programming language Key wordsAndroid Game, Action Game, Arcade Game, Augmented Reality, Camera, Fly Shooter